Distinct lobes of Limulus ventral photoreceptors. II. Structure and ultrastructure (The Rockefeller University Press, 1982)
The structure of Limulus ventral photoreceptors fixed in situ has been investigated using light and electron microscopy and computer-assisted reconstruction and planimetry. Photoreceptors occur singly and in clusters. All photoreceptors have two types of lobes. The rhabdomeral lobe (R lobe) appears to be specialized for light sensitivity, containing the rhabdomere, which completely covers its external surface and forms infoldings into the lobe. The structure of the external rhabdom differs from that within infoldings. The other main structures of the R lobe are the palisades along the rhabdom, multivesicular bodies, lamellar bodies, and mitochondria. The arhabdomeral lobe (A lobe) bears the axon and contains the nucleus, clusters of residual bodies, lamellar arrays of endoplasmic reticulum, masses of glycogen, lipid droplets, and Golgi complexes. The R lobe and A lobe are analogous to the outer and inner segments of vertebrae photoreceptors. In single photoreceptors A and R lobes are separated by an indentation filled with glial processes. Computer reconstructions of cell clusters reveal that each cell has both types of lobes and an axon. Most of the rhabdom is formed from abutting arrays of external rhabdom from the R lobes of different members of the cluster. Efferent fibers containing characteristic angular granules penetrate single cells and clusters in glial invaginations. The main, if not exclusive, target of the efferent fibers is the internal rhabdom.